Dual axis solar tracker study - Lim, Zi Chao (2010)
An analysis for a dual axis solar tracking study is to be carried out. In the current growth of technology, the technology of this dual axis solar tracking system has not been fully utilized. The other solar power system called single axis solar power system is much more popular and widely used. However, single axis solar tracking system has a very low efficiency, yet it is not cost effective. Therefore, the analysis of dual axis solar tracking system is to be carried out to take over the inefficient single axis solar tracking system. An independent method will be used in order to evaluate the performance of the proposed tracking system. It is by practically using a dummy solar tracker to test whether the reflection of the sun is accurately towards the target point at any given time according to the mathematical calculation of the elevation and azimuth angles of the sun. A simulation using Borland C++ Builder will be created to simulate the processes and the steps to operating a real dual axis solar tracker. At the end of this project, it is expected that the azimuth-elevation angles calculated are precise and accurate at any place and time.